The family Isoetaceae in Guerrero, Mexico: A new record - Ernesto Velázquez-Montes (Botan‪ical Sciences, 2014)
Despite the intensive taxonomic studies on pteridophytes carried out in Mexico, particularly in the state of Guerrero, the monotypic family Isoetaceae has not yet been reported in this area. This is probably because its rarity in the field, and its gross morphology and growth habit resemblance to some grasses and other aquatic plants. As recorded in this article, Isoetes pallida has for the first time been confirmed on the southeastern coastal plain near Acapulco, constituting the third record of this taxon in the country and the first in the state of Guerrero. Currently, the color and ornamentation of the sporangial wall are used to separate some species of Isöetes, but the taxonomic value of these characteristics seems to be questionable.